Mega Sporting Event Legacies: A Multifaceted Concept - Chappelet, Jean-Loup (Papeles de Europa, 2012)
The legacy of mega sporting events can be perceived in several ways. It can be seenas positive or negative, tangible or intangible, territorial or personal, intentional orunintentional, global or local, short- or long-term, sport- or non sport-related, and canalso be seen from the various event stakeholders’ perspectives. In fact, it is muchmore appropriate to talk about legacies in the plural than simply legacy. This papergives a broad overview of an often used but rarely defined concept, using examplesfrom the legacies of the Olympic and Commonwealth Games, arguably two of themost important mega sporting events. It concludes that legacy essentially is a dreamto be pursued rather than a certainty to be achieved.
Keywords: Commonwealth Games; impact; legacy; Olympic Games